The Role of Nutrition and Hydration in Injury Prevention and Recovery: A Review - Jakub Chodkowski (Journal of Education, Health and Sport)
Introduction and Purpose: Nutrition and hydration play critical roles in supporting athletic performance, injury prevention, and effective recovery, impacting both amateur and elite athletes. This literature review explores current evidence on nutritional and hydration strategies that promote musculoskeletal health, reduce injury risk, and optimize recovery following injury.